Community Pharmacy: The Role of Strategy in Increasing Access and Quality of Health Services - Rochmah, Nikmah Nuur; Winata, Norma (Pt. Anagata Sembagi Education, 2025)
This study aims to analyze the strategic role of community pharmacies in improving access to and quality of healthcare services. The research method used was qualitative with a descriptive approach. Data were collected through in-depth interviews with pharmacists, patients, and stakeholders, observations of pharmacy services, and documentation studies related to operational standards and policies. Data analysis was conducted using the Miles & Huberman model through data reduction, data presentation, and conclusion drawing. The results showed that the strategies implemented by community pharmacies include expanding operating hours, digitizing services, providing medication delivery services, improving pharmacist competency, and implementing pharmaceutical service standards. These strategies have had a positive impact on improving public access to pharmaceutical services and the quality of healthcare services. However, challenges remain, including limited human resources, technological constraints in certain regions, and suboptimal regulations. This study confirms that community pharmacies have a strategic role in supporting the primary healthcare system and need to be supported by more comprehensive policies.